EVALUATING INTEREST IN VOCATIONAL PROGRAMS IN ANAMBRA STATE, NIGERIA: DOES CREATIVE THINKING AND OPEN-MINDEDNESS MATTER? - Awele Vivian, Ekwezia (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The government's dedication to ensuring that students acquire technical and vocational skills for self-development and economic growth is reflected in the integration of the TVET program into Nigeria's educational ecosystem. Nevertheless, signs point to a decrease in students enrolling in vocational programs. The current study aimed to determine whether secondary school students were interested in the TVET program based on critical thinking and open-mindedness. The study involved 233 secondary school students from public and private institutions in Anambra State. 13 (12.4%) respondents were 17 years old, 103 (58.0%) respondents were 16 years old, and 87 (25.6%) respondents were 15 years old. Among the respondents were 84 males (41.0 percent) and 119 females (59.0 percent). They filled out self-report questionnaires on their interest in TVET, their level of creativity, and their level of open-mindedness. The results showed that creative thinking ( =.183, p .001) and open-mindedness ( = 168, p .001) among secondary school students in Anambra State were significant predictors of student interest in vocational programs. The two predictor variables explained the total variance in the students' interest in vocational programs to 42.2%. The study's conclusions and practical implications are discussed.